Zebrafish as a model to understand autophagy and its role in neurological disease() - Fleming, Angeleen (Elsevier Pub. Co, 2011)
In the past decade, the zebrafish (Danio rerio) has become a popular model system for the study of vertebrate development, since the embryos and larvae of this species are small, transparent and undergo rapid development ex utero, allowing in vivo analysis of embryogenesis and organogenesis. These characteristics can also be exploited by researchers interested in signaling pathways and disease processes and, accordingly, there is a growing literature on the use of zebrafish to model human disease. This model holds great potential for exploring how autophagy, an evolutionarily conserved mechanism for protein degradation, influences the pathogeneses of a range of different human diseases and for the evaluation of this pathway as a potential therapeutic strategy. Here we summarize what is known about the regulation of autophagy in eukaryotic cells and its role in neurodegenerative disease and highlight how research using zebrafish has helped further our understanding of these processes.